WRITING FOR BEGINNERS A COMPLETE GUIDE TO BECOMING AN EFFECTIVE WRITER - Abdurrahman Adrian; Anita Firdaus, Checilya Anastasya Panggabean, Cut Fara Vhiqia Yusuf, Salman Rawin Siregar, Morada Te (International Journal of Teaching and Learning, 2025)
The ability to write well and effectively is an important skill to master, especially for beginning writers. This paper aims to guide budding writers to become effective writers. It will discuss the problems faced by a novice writer and tips to become an effective writer. The method used is a qualitative literature study approach (library research). The result is that qualitative research is carried out with a research design whose findings are not obtained through statistical procedures or in the form of counts but aim to reveal phenomena in a holistic- contextual manner by collecting data from natural settings and utilizing researchers as key instruments. Data collection is done by finding sources and reconstructing from various sources, such as books, journals, articles, and existing research. This qualitative research design can be used as a method in research because the design is described in a comprehensive manner that is easy for researchers and academics to understand.